ANALYSIS OF STRIPED CATFISH (Pangasianodon hypophthalmus) HATCHERY BUSINESS AT THE TUNAS MUDA FISH FARM PEOPLE'S HATCHERY UNIT IN KUOK DISTRICT KAMPAR REGENCY RIAU PROVINCE - Rahmaditullah, Rahmaditullah; Hendrik, Hendrik; Zulkarnaini, Zulkarnaini (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2022)
Kampar Regency is one of the largest producers of catfish cultivation in Riau Province, where in 2020 the total production can reach 32,401 tons. The catfish cultivation business has the largest increase every year compared to other fish farming businesses, thereby increasing the demand for catfish seeds from the people's hatchery business (UPR). UPR Tunas Muda Fish Farm is a striped catfish hatchery located in Kuok District, Kampar Regency, Riau Province. This hatchery business needs to be developed for its business in order to increase production yields even more. To develop this business, it is necessary to first know the feasibility level of the business. This research can be used as a study to determine the feasibility level of this hatchery business by analyzing an investment, profits, and Calculation of Revenue Cost of Ratio (RCR), Financial Rate of Return (FRR), and Payback Period of Capital (PPC). This research was conducted on 23 May – 05 June 2021 at UPR Tunas Muda Fish Farm. The method used in this research is the case study method. Respondents taken in this study were owners and all workers. The results showed that the total investment invested in this hatchery business was Rp.291.170.000. The annual profit earned is Rp.142.654.000. The RCR value obtained is 1.4, the FRR value obtained is 49%, and the PPC value obtained is 17 production periods or 2.1 years.